Digitalization, Current Working Conditions and Environment: Comparative Study of Several Countries in ASEAN - Suryadi, Suryadi; Nasution, Faizal Amir P (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2024)
Digital technology changes the way of work. It can improve connections between an organization's technical and social systems as well as connections with external networks through the sharing and exchange of digital information. The average worker in ASEAN wants a salary increase and wants a promotion, and some others want to change jobs. Respondents who want to change jobs come from Indonesia. Most respondents in ASEAN want job satisfaction, and many believe that job skills will change in the next five years. Apart from that, most respondents in ASEAN also believe that their organizations will be able to stay in business for more than 10 years. Respondents from Indonesia rated the highest on variables related to workplace culture, empowerment, fairness and feedback. Meanwhile, respondents from the Philippines gave the lowest assessment to variables related to new job opportunities, opportunities to learn new skills and increased productivity with the presence of artificial intelligence. Employee welfare needs to be a priority for companies, so companies need to collect data about employee desires and motivations, segment employees and prioritize action plans for management in the company.